Some experiences of radar observation of cyclonic storms in the southern Bay of Bengal - RAGHAVAN, S.; RENGARAJAN, S.; VARADARAJAN, V. M. (MAUSAM, 1980)
From a study of eight cyclonic storms observed with the Cyclone Warning Radar, Madras from 1972 to 1977 an assessment of the information obtainable by radar on cyclones in the Indian seas is attempted. Storms in this part of the Bay may be divided broadly into two categories: (i) well developed ones exhibiting a distinct eye and other features generally associated with hurricanes and typhoons and (ii) immature ones which do not have well developed banding. The latter are difficult to track by radar though useful information can be obtained regarding their structure. Cyclones in the former category can usually be tracked from a range of about 300 to 350 km. Fixes in initial stages have to be co-ordinated very closely with satellite and synoptic evidence, and may have a wide margin of error. Usual radar predictors of storm motion such as echo concentration etc are not reliable for any individual storm. Extrapolation of radar track is usually successful except in cases of recurvature. Radar gives considerable operationally useful information on size and shape of the eye, areal extent of precipitation, location of sectors of intense precipitation and structure of clouds in different sectors. Shrinkage of the eye usually indicates intensification. Persistent changes in degree of organisation over long periods appear to be a sign of change in, storm intensity; changes with time in heights and intensities of individual clouds of the eyewall of a given storm appear correlated with storm intensity. Information on areal distribution of echoes can probably be used in realtime while issuing warnings.